Modelling of flow boiling process in small diameter tubes - Mikielewicz, Dariusz (Strojniški vestnik, 2005)
In the paper presented is application of a correlation describing flow boilingdata, developed for conventional tubes, to small diameter tubes. Comparison between data from literature and calculated values has been made, which gives poor agreement and indicates that substantially more research is required to develop correlations with theoretical foundations to predict heat transfer in small diameter channels.
Keywords: tok dvofazni; tok v cevi; modeliranje; procesi vrenja; vrenje; cevi